James Herriot's Treasury for Children - Herriot, James; Brown, Ruth; Barrett, Peter, 1935- (New York : St. Martin's Press, 1992)
A collection of the author's stories for children, including "Moses the Kitten," "The Market Square Dog," and "Smudge, the Little Lost Lamb."
Keywords: Pets -- Biography -- England; Domestic animals -- Biography -- England; Farm life -- Juvenile literature. -- England; Animals; Farm life